Entre a fábrica e a senzala: um estudo sobre o cotidiano dos africanos livres na Real Fábrica de Ferro São João do Ipanema - Sorocaba - SP (1840-1870) - Ribeiro, Mariana Alice Pereira Schatzer [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This thesis intend to analyze the experience of free Africans in an imperial factory environment, the Fábrica de Ferro São João do Ipanema, located in Sorocaba – SP, searching to see them as historical subjects, inserted in the slavery and active resistance of such a system relations. This study is a sequence of work done in scientific research developed during the year of 2010, which we examine the life of slave laborers between 1835-1838. As already held a work with the slaves, called Creoles, our intention now is to study the free Africans, a group of important workers to the history of 1880’s year Brazil. Thus, will be observed their ethnic origins, occupied functions, leaks, conflict, health, diseases, family arrangements, and their conceptions of freedom. The main sources for the study are the crafts, listings and correspondence arising from the establishment, which are under the custody of the Public Archive of Sao Paulo State. An examination of documentation also showed that the relationship of workers led to the creation and strengthening of the bonds between mates. In practice, African and slaves suffered no differences in daily life, such as jobs, food, housing and other factors. Therefore, the right to freedom after 14 years of service was not often effective, which confirms the idea that their condition was only a legal status of law for show

Esta dissertação pretende analisar a experiência dos africanos livres em um ambiente fabril imperial, a Fábrica de Ferro São João do Ipanema- Sorocaba-SP. Buscando vê-los como sujeitos históricos, inseridos nas relações escravistas e atuantes à resistência de tal sistema. Esta pesquisa é uma continuidade do trabalho feito na iniciação científica desenvolvida durante o ano de 2010, na qual analisamos a vida dos escravos operários entre 1835 a 1838. Como já realizamos um trabalho com os escravos, ditos crioulos, nossa intenção agora é estudar os africanos livres, grupo de trabalhadores importantes para a história do Brasil oitocentista. Desse modo, observaremos suas origens étnicas, funções ocupadas, fugas, conflitos, saúde, doenças, arranjos familiares, bem como as suas concepções de liberdade. As fontes principais para o estudo são os ofícios, as listagens e correspondências oriundas do estabelecimento, os quais estão sob a guarda do Arquivo Público do Estado de São Paulo. O exame da documentação mostrou também que o relacionamento dos trabalhadores levava à criação e ao fortalecimento dos laços entre companheiros. Na prática, africanos e escravos não sofreram diferenciações no cotidiano, como tarefas, alimentação, moradia entre outros fatores. Por conseguinte, o direito à liberdade após os 14 anos de serviços prestados muitas vezes não se efetivou, comprovando assim, a ideia de que sua condição foi somente um status jurídico da “lei para inglês ver”
Keywords: Escravidão; Africanos; Fabricas; History; Brasil - Historia - Imperio - 1822-1889